C(60) fullerene restores gastrocnemius contractile activity in a rat model of neurogenic muscle atrophy - M. S. Anhelov; T. Yu. Matviienko; O. V. Lynchak; O. V. Korzhyk; Yu. M. Valetskyi; K. I. Bogutska; Yu. I. Prylutskyy (The Ukrainian Biochemical Journal, 2025)
Restoration of the motor function of the musculoskeletal system impaired due to innervation damage is an important clinical problem. In the study the potential therapeutic effect of C60 fullerene application was estimated in the Wistar rat model of neurogenic muscle atrophy caused by nervus ischiadicus injury. The animals were divided into the following: control, injury, injury+С60 groups. C60 fullerene aqueous solution was administrated orally for 30 days after ischiadicus injury at a daily dose of 1 mg/kg. Biomechanical parameters of gastrocnemius muscle contraction and biochemical indices (creatinine, lactate, reduced glutathione content as well as creatine phosphokinase, lactate dehydrogenase, catalase and superoxide dismutase activity) in the blood of rats were estimated on day 30 after nerve transection. It has been found that muscle strength response in the injury+С60 group was significantly enhanced, in particular, the muscle force impulse was increased by more than 30 ± 2% compared to the injury group. The studied biochemical indices of the muscle fatigue and oxidative stress in the blood of experimental animals had a pronounced tendency to increase after the initiation of the muscle neurogenic atrophy, while under the influence of C60 fullerene they decreased compared with the injury group. In our opinion, C60 fullerene prevented significant dysfunction of the gastrocnemius muscle after neurogenic atrophy by exerting an antioxidant effect and improving its contractile activity.